Analisis Spasial Tingkat Kriminalitas Kabupaten/Kota di Provinsi Sumatera Utara Tahun 2022 - Sinaga, Vhania Mutiara; Pasaribu, Ernawati (Politeknik Statistika STIS, 2025)
Security from crime is a fundamental human right, highlighted in Goal 16 of the Sustainable Development Goals (SDGs). Indonesia continues to experience relatively low safety levels, with North Sumatera Province significantly contributing to the national crime rate. The high criminality in this region is influenced by social, economic, demographic, and political factors, and spatial effects, where crime rates in one area can impact neighboring regions. This study aims to analyze crime levels in North Sumatera while incorporating these spatial effects. Utilizing secondary data from Badan Pusat Statistik, the analysis employs the Geographically Weighted Regression (GWR) method, which accounts for spatially varying relationships between variables using Fixed Gaussian weighting based on constant spatial distances. The findings reveal spatial heterogeneity, indicating differing relationships across regions. Five independent variables significantly affecting crime levels include average years of schooling, population density, per capita expenditure, number of police officers, and the Gini ratio.